Metronidazole response profiles of Gardnerella species are congruent with phylogenetic and comparative genomic analyses - Innamorati, Katherine A.; Earl, Joshua P.; Barrera, Shirley C.; Ehrlich, Rachel L.; Aiyeku, Josephine; Gordon, Ari; Powell, Evan; Retchless, Adam C.; Ahmed, Azad; Sen, Bhaswati; Balashov, Sergey; Mell, Joshua Chang; et al. (Genome medicine, 2025)
Bacterial vaginosis (BV) affects 20-50% of reproductive-age female patients annually, arising when opportunistic pathogens outcompete healthy vaginal flora. Many patients fail to resolve symptoms with a course of metronidazole, the current first-line treatment for BV. Our study was designed to identify genomic variation associated with metronidazole resistance among strains of Gardnerella vaginalis spp. (GV), a genus of biogenic-amine-producing bacteria closely associated with BV pathogenesis, for the development of a companion molecular diagnostic. Whole-genome sequencing and comparative genomic metrics, including average nucleotide identity and GC content, were performed on a diverse set of 129 GV genomes to generate data for detailed taxonomic analyses. Pangenomic analyses were employed to construct a phylogenetic tree and cluster highly related strains within genospecies. G. vaginalis spp. clinical isolates within our collection were subjected to plate-based minimum inhibitory concentration (MIC) testing of metronidazole (n = 60) and clindamycin (n = 63). DECIPHER and MAFFT were used to identify genospecies-specific primers associated with antibiotic-resistance phenotypes. PCR-based analyses with these primers were used to confirm their specificity for the relevant genospecies. Eleven distinct genospecies based on standard ANI criteria were identified among the GV strains in our collection. Metronidazole MIC testing revealed six genospecies within a closely related phylogenetic clade contained only highly metronidazole-resistant strains (MIC ≥ 32 µg/mL) and suggested at least two mechanisms of metronidazole resistance within the eleven GV genospecies. All strains within the six highly metronidazole-resistant genospecies displayed susceptibility to clinically relevant clindamycin concentrations (MIC ≤ 2 µg/mL). A PCR-based molecular diagnostic assay was developed to distinguish between members of the metronidazole-resistant and mixed-response genospecies, which should be useful for determining the clade membership of various GV strains and could assist in the selection of appropriate antibiotic therapies for BV cases. This study provides comparative genomic and phylogenetic evidence for eleven distinct genospecies within the genus Gardnerella vaginalis spp., and identifies genospecies-specific responses to metronidazole, the first-line treatment for BV. A companion molecular diagnostic assay was developed that is capable of identifying essentially all highly metronidazole-resistant strains that phylogenetically cluster together within the GV genospecies, which is informative for antibiotic treatment options.